2014
DOI: 10.1016/j.neo.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab Induces Eme1-Mediated DNA Repair: a Novel Mechanism for Cetuximab Resistance

Abstract: Overexpression of the epidermal growth factor receptor (EGFR) is observed in a large number of neoplasms. The monoclonal antibody cetuximab/Erbitux is frequently applied to treat EGFR-expressing tumors. However, the application of cetuximab alone or in combination with radio- and/or chemotherapy often yields only little benefit for patients. In the present study, we describe a mechanism that explains resistance of both tumor cell lines and cultured primary human glioma cells to cetuximab. Treatment of these ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…However, we observed that PIC–Nal–IRI transiently downregulates γ-H2AX expression in the first 24 h of incubation. This is presumably due to the activation of Cet-induced DNA repair pathways (e.g., Eme1) as shown by others [47]. Lastly, depolarization of the mitochondrial membrane was observed at 24 h after light activation of PIC–Nal–IRI, PIC-Nal, or PIC, but not with Nal–IRI alone, suggesting cytosolic mitochondrial photodamage is achieved primarily by PIC, as reported by us [9].…”
Section: Discussionsupporting
confidence: 72%
“…However, we observed that PIC–Nal–IRI transiently downregulates γ-H2AX expression in the first 24 h of incubation. This is presumably due to the activation of Cet-induced DNA repair pathways (e.g., Eme1) as shown by others [47]. Lastly, depolarization of the mitochondrial membrane was observed at 24 h after light activation of PIC–Nal–IRI, PIC-Nal, or PIC, but not with Nal–IRI alone, suggesting cytosolic mitochondrial photodamage is achieved primarily by PIC, as reported by us [9].…”
Section: Discussionsupporting
confidence: 72%
“…Weinandy et al ( 89 ) suggested that Eme1 protein is significantly increased under cetuximab resistance, which often means that treatment may fail. Mechanistically, elevated levels of Mus81/Eme1 endonuclease during cetuximab treatment promoted DNA repair and ultimately led to tumor cell growth.…”
Section: Mechanisms Of Egfr Antibody Resistancementioning
confidence: 99%
“…The administration of mAb 806 has shown promising results in preclinical glioma models. 36,37 However, data on its putative clinical activity are still lacking. Further strategies include the administration of antibody-drug conjugates (ADCs), which consist of an anti-EGFR antibody conjugated to potent cytotoxic drugs.…”
Section: Anti-egfr Antibodiesmentioning
confidence: 99%